Association between social activities and risk of COVID-19 in a cohort of healthcare personnel - Holly Shoemaker; Haojia Li; Yue Zhang; Jeanmarie Mayer; Michael Rubin; Candace Haroldsen; Morgan M. Millar; Per H. Gesteland; Andrew T. Pavia; Lindsay T. Keegan; Jessica Marie Cole; Egenia Dorsan; et al. (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract